2002
DOI: 10.1515/znc-2002-3-426
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant Production By A New Pseudomonas Putida Strain

Abstract: Biosurfactants, Rhamnolipids, Pseudomonas putidaObservation of both tensio-active and emulsifying activities indicated that biosurfactants were produced by the newly isolated and promising strain Pseudomonas putida 21BN. The biosurfactants were identified as rhamnolipids, the amphiphilic surface-active glycolipids usually secreted by Pseudomonas spp. Their production was observed when the strain was grown on soluble substrates, such as glucose or on poorly soluble substrates, such as hexadecane, reaching value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 2 publications
5
57
0
11
Order By: Relevance
“…Pseudomonas aeruginosa has been widely studied and is known to produce a glycolipid type of biosurfactant [34,35]. Rhamnolipids are amphiphilic surface-active glycolipids that are usually secreted in the growth medium [36,37], but can potentially be used to combat marine oil pollution [8]. Figure 5 shows that the value of MATH increased from 0.71 to 0.91 when B1 was cultured with hexadecane.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa has been widely studied and is known to produce a glycolipid type of biosurfactant [34,35]. Rhamnolipids are amphiphilic surface-active glycolipids that are usually secreted in the growth medium [36,37], but can potentially be used to combat marine oil pollution [8]. Figure 5 shows that the value of MATH increased from 0.71 to 0.91 when B1 was cultured with hexadecane.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a variety of different hydrophobic substrates were efficiently emulsified by P. aeruginosa strain KVD-HR42 supernatant. It was reported in a study that nhexadecane was attracted to the cell surface of the 21 BN strain of P. putida at a rate of 72% (Tuleva et al, 2002). In a different study by Noordman and Janssen (2002), it was found that n-hexadecane was attracted to the cell surfaces of the strains of biosurfactant producer P. aeruginosa 18 UG2, Acinetobacter calcoaceticus RAG1, Rhodococcus erythropolis DSM 43066, and Rhodococcus erythropolis ATCC 19558 at rates of 42, 81, 30, and 12%, respectively.…”
Section: Emulsification Activitymentioning
confidence: 99%
“…The cell surfaces of the strains attracted benzene at a rate of 73% and 62%, n-hexane at a rate of 40% and 29%, toluene at a rate of 65% and 72%, and xylene at a rate of 60% and 53%, respectively (Table 4). It was reported in another study that n-hexadecane was attracted to the cell surface of the 21 BN strain of P. putida at a rate of 72% (Tuleva et al, 2002). In a study by Noordman and Janssen (2002) at rates of 42%, 81%, 30%, and 12%, respectively.…”
Section: Emulsification Activity and Cell Surface Hydrophobicitymentioning
confidence: 92%